Advances in antitumor research of CA-4 analogs carrying quinoline scaffold - Wang, Chao; Chang, Jing; Yang, Shanbo; Shi, Lingyu; Zhang, Yujing; Liu, Wenjing; Meng, Jingsen; Zeng, Jun; Zhang, Renshuai; Xing, Dongming (Frontiers in Chemistry, 2022)
Combretastatin A-4 (CA-4) is a potent inhibitor of tubulin polymerization and a colchicine binding site inhibitor (CBSI). The structure-activity relationship study of CA-4 showed that the cis double bond configuration and the 3,4,5-trimethoxy group on the A ring were important factors to maintain the activity of CA-4. Therefore, starting from this condition, chemists modified the double bond and also substituted 3,4,5-trimethoxyphenyl with various heterocycles, resulting in a new generation of CA-4 analogs such as chalcone, Flavonoid derivatives, indole, imidazole, etc. Quinoline derivatives have strong biological activity and have been sought after by major researchers for their antitumor activity in recent years. This article reviews the research progress of novel CA-4 containing quinoline analogs in anti-tumor from 1992 to 2022 and expounds on the pharmacological mechanisms of these effective compounds, including but not limited to apoptosis, cell cycle, tubulin polymerization inhibition, immune Fluorescence experiments, etc., which lay the foundation for the subsequent development of CA-4 containing quinoline analogs for clinical use.